2021
DOI: 10.1029/2020jc017091
|View full text |Cite
|
Sign up to set email alerts
|

Physical Controls on the Macrofaunal Benthic Biomass in Barrow Canyon, Chukchi Sea

Abstract: The Chukchi Sea is one of the most productive regions of the Arctic Ocean (Springer & McRoy, 1993), in part because of the high levels of nutrients advected through the Bering Strait (Grebmeier, Bluhm, et al., 2015). Furthermore, due to the recent decline in sea ice cover and higher percentage of thin first-year ice, light levels have increased which has led to even larger levels of annual production (Arrigo & van Dijken, 2011). Since the Chukchi shelf is an export-dominated regime, the large amount of carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…have extended their distribution northward with warming seawater [53]. Of note, DBO5 stations in Barrow Canyon do not show increased bottom water temperatures, likely due to its dynamic nature and the seasonally variable water masses reported there [54]. Finally, increasing bottom water salinity since 2019 in DBO2 is perhaps indicative of a stronger Anadyr water signal at depth that may also influence nutrient availability to surface waters by mixing upward of AW after storm events.…”
Section: Environmental Factors and Pelagic-benthic Couplingmentioning
confidence: 93%
“…have extended their distribution northward with warming seawater [53]. Of note, DBO5 stations in Barrow Canyon do not show increased bottom water temperatures, likely due to its dynamic nature and the seasonally variable water masses reported there [54]. Finally, increasing bottom water salinity since 2019 in DBO2 is perhaps indicative of a stronger Anadyr water signal at depth that may also influence nutrient availability to surface waters by mixing upward of AW after storm events.…”
Section: Environmental Factors and Pelagic-benthic Couplingmentioning
confidence: 93%
“…The 10-m wind data were obtained from the meteorological station at Utqiaġvik, Alaska (magenta star in Figure 1b). The data well represent the regional wind condition in the vicinity of Barrow Canyon (Pickart et al, 2019(Pickart et al, , 2021. The data have been quality controlled and interpolated onto an hourly interval (see Pickart, Schulze, et al, 2013 for the details).…”
Section: Wind Datamentioning
confidence: 99%
“…Pickart et al. (2021) revealed that the flow accelerates as converging into the canyon, resulting in a strong downwelling on this cyclonic side (northwestern side) of the flow. The downwelling feeds the biological processes to the seabed and thus contributes a benthic “hotspot” in the Barrow Canyon.…”
Section: Introductionmentioning
confidence: 99%
“…These observations are particularly important given the extensive environmental changes observed throughout the region over the past few decades. Numerous recent studies have illustrated the importance of climate warming for ecosystem dynamics throughout the DBO sites [38][39][40][41][42][43]. While there have been recent satellite- Basemap datasets from Natural Earth [49] and ESRI [50].…”
Section: Introductionmentioning
confidence: 99%